Mengelola Biaya Modal Melalui Kinerja Tanggung Jawab Sosial Perusahaan Dan Kepemilikan Institusional Sebagai Variabel Moderasi: Studi Dalam Industri Perhotelan, Pariwisata, Dan Restoran Di Indonesia Dan Malaysia - Joel Caesar Cornelius; Stephanie Sugianto; Saarce Elsye Hatane (Business Accounting Review, 2020)
This study aims to determine whether there is a relationship between CSR performance and institutional ownership towards the company’s cost of capital in the hospitality, tourism and restaurant industry in Indonesia and Malaysia. The hypothesis of this study was tested using a panel data regression model that was managed using Gretl application. Objects of this research are 48 companies in hospitality, tourism, and restaurant industry that have published annual financial reports and were published on Indonesia Stock Exchange (IDX) and Malaysia Stock Exchange (MYX) during 2014-2019. Statistical results show that CSR performance increases cost of capital, while institutional ownership has a negative impact on cost of capital.